In-silico Analysis of Phytocompounds Identified by GC-MS from Moringa oleifera Leaves of Kolli Hills at Namakkal Against Colorectal Cancer: Life Sciences-Biotechnology - S, Sowmiya; Jasmine, R.; A, Sherlin Rosita; V, Bharathi; M, Keerthiga (International Journal of Life Science and Pharma Research, 2023)
Plants have been used for medicinal purposes long before the prehistoric period. The use of plants and natural substances to cure a wide range of human ailments has become increasingly popular due to the population explosion, insufficient drug supply, high cost of treatments, adverse effects of various synthetic medications, and the emergence of drug resistance. Because of its potent healing properties, India views Moringa oleifera as a "mystical plant." These phytochemicals made by plants have the potential to take the place of antibiotics, antihelminthicides, and antivirals in the fight against a range of pathogenic diseases. The aim of this current study is to evaluate the M. oleifera leaf aqueous extract compounds against Colorectal cancer through In-silico analysis. The objective of this research is to analysis the phytocompounds present in the extract of Moringa oleifera from the Kolli Hills region, identify the biologically active compounds through GC-MS, and determine whether In-silico analysis reveals anticancer activity. The GC-MS analysis, which indicates 10 peaks of biomolecules such as Hexatriacontane, 2- Hexadecen-1-Ol, 3,7,11,15-Tetramethyl-, [R- [R*, R*-(E)], Neophytadiene, Docosane, Benzenepropanoic Acid, Alpha. -[(Trimethylsilyl)Oxy]-, Trimethylsilyl, Tetracosane, Succinic acid, epicotyl 3-methylbut-3-enyl ester , 2,3,4,5,6-Pentafluorobenzyl Crotonate , Acetic acid, 2-(9-phenylimino-10-acridanyl)- , ethyl ester , Butane, 1,1-diethoxy-3-methyl- . Docking studies with β-catenin revealed that Acetic acid, 2-(9-phenylimino-10-acridanyl)-ethyl ester, has minimum docking scores and high binding affinity against β-catenin of Human Colorectal cancer, indicating that M. oleifera from Kolli Hills region has a promising natural bioactive source and might be a valuable source for future anti-cancer therapy especially Colorectal cancer. The novelty of this study is that no report has yet been cited on the effectiveness of M. oleifera extracts obtained from the Kolli hills region as an anti-cancer agent against Colorectal cancer.